Melampaui Antropocentrism: Ekoteologi dan Etika Lingkungan dalam Dialog, Sebuah Pendekatan Interdisipliner Untuk Keberlanjutan dan Keadilan Ekologis - Sumule, Linus (Sekolah Tinggi Teologi Abdiel, 2024)
The current ecological issue has become a global challenge, one of the triggers of the current ecological issue is the human understanding that considers itself superior and anthropocentric. Responding to these fundamental problems needs to be addressed for the future sustainability of the earth. Interdisciplinary theology is present as an approach that bridges one or more disciplines to direct global issues that are being wrestled with. This research uses descriptive qualitative methods, collection and development of information through literature studies to answer the problem formulation being studied. The description contains ecological problems and interdisciplinary dialogues between eco-theology and environmental ethics to direct anthropocentric attitudes as the root of ecological problems. This research aims to provide new breakthroughs towards sustainability and ecological justice. The results of the study show that interdisciplinary theology provides a relevant and profound foundation for facing ecological challenges and shifting the human paradigm as a ruler of nature towards a wise and sustainable attitude.